The Relation Between Academic Procrastination, Symptoms of Attention Deficit Hyperactivity Disorder and Academic Performance in Medical Students - Sonmez, Ozge; Koyuncu, Zehra; Atlı, Zeynep; Hacıkerimoğlu, Özlem; Tekgöl, Nermin Cansu; Kadak, Muhammed Tayyib (Cerrahpaşa Medical Journal, 2023)
Objectives: Procrastination is putting off intended tasks which are necessary to reach a goal. Attention Deficit Hyperactivity Disorder (ADHD) is characterized by excessive inattention, impulsivity, and hyperactivity. We aimed to understand association between academic performance, procrastination and ADHD. Methods: A group of medicine students screened for procrastination and ADHD by self-report scales. First, second, third and fourth year medicine students were included in the study. Background information including birth orders, parents’ education status, department satisfaction, sex and age were collected. Tuckman Procrastination scale and adult ADHD self-report scale were applied. Grade point average (GPA) was noted and it was accepted as an indicator of academic performance. Results: A total of 318 (age:19.7 1.6; 46% male) volunteer medicine students was included. Student with lower GPA had higher tendency to procrastinate than those with high. Even though ADHD self-reported scores were positively correlated with procrastination scores, regression analyses showed that there was not statistically significant association between ADHD symptoms and academic performance. Conclusion: In conclusion, procrastination leads to poor academic performance and nearly half of the students had a tendency to procrastinate. Moreover, students with probable ADHD symptoms were tended to procrastinate more. Therefore, students with poor academic performance might be screened for procrastination and ADHD symptoms.